ERP Systems in the hospitality industry: value creation and critical success factors - Azevedo, Paula Serdeira (2013)
The purpose of this paper is to highlight factors that may be considered critical to successful use of ERP (Enterprise Resource Planning) systems in the hospitality industry, in particular those that seem to be limiting a broader usage of these systems in this industry. The paper also contributes to the understanding of how ERP systems may create value to these industry´s businesses. This is done through a reference model, providing the framework to understand how the current vendor´s offer fits into the business needs of this industry.